Analysis of FinTech Usage Behavior Model among Minang Traders: The Mediating Role of Behavior Intention and the Influence of Perceived Risk and Habit - Yuhelmi, Yuhelmi; Yunilma, Yunilma; Trianita, Mery; Yolanda, Yolanda (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2026)
This study examines how user behavior (UB) in financial technology transactions can help Minang traders. Factors considered include perceived ease of use (PEOU), perceived usefulness (PU), self-efficacy (SE), habits (H), perceived risk (PR), attitudes (A), and behavioral intentions (BI). The study focused on individual Minang business owners and financial operators, with a convenience sample of 178 respondents. Path analysis using SmartPLS was applied. Results show PEOU positively affects PU, but not BI directly. However, PEOU indirectly affects BI through PU, which in turn influences BI. BI does not mediate between PEOU and user behavior (UB), but PU and BI together do. Habit (H) has a positive effect on both BI and UB, and BI partially mediates the effect of H on UB. PR negatively affects UB but not BI, so BI does not mediate the PR effect on UB. However, BI does mediate the effect of PU on UB, as BI influences UB